Pengaruh Pemberian Jus Daging Buah Jambu Biji (Psidium guajava) Terhadap Penurunan Kolesterol Pada Pasien Hiperkolesterolemia: The Administration Effect from Guava Fruit Juice (Psidium guajava) Towards Cholesterol Reduction on Hypercholesterolemia Patients - Nadiyah Amalia Aprilliani; Hajrah Hajrah; Hadi Kuncoro (Proceeding of Mulawarman Pharmaceuticals Conferences, 2021)
Red guava (Psidium guajava) fruits contain lots of vitamin C with 183,5 mg/ 100g. Vitamin C has been researched to have an antioxidant activity that can lower total cholesterol levels. This study aims to analyze meat guava juice's effect in reducing total cholesterol levels in hypercholesterolemia patients in Samarinda. The research method is quasi-experimental, pre-test and post-test with control design, with purposive sampling as a sampling method. In the study research, as many as ten people were divided into two groups, group one was given a dose of 250 g once a day, and group two was given a dose of 125 g twice a day and both treatments were given 14-days. Cholesterol data is taken by strip-test method and data analysis using paired T-Test. The analysis results obtained a p-value for the treatment group one of 0.018, for treatment group two of 0,00, and the difference between groups one and two of 0,00. The analysis results showed p-value